2020
DOI: 10.1371/journal.pone.0244683
|View full text |Cite
|
Sign up to set email alerts
|

Noise suppression ability and its mechanism analysis of scale-free spiking neural network under white Gaussian noise

Abstract: With the continuous improvement of automation and informatization, the electromagnetic environment has become increasingly complex. Traditional protection methods for electronic systems are facing with serious challenges. Biological nervous system has the self-adaptive advantages under the regulation of the nervous system. It is necessary to explore a new thought on electromagnetic protection by drawing from the self-adaptive advantage of the biological nervous system. In this study, the scale-free spiking neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
(56 reference statements)
0
3
0
Order By: Relevance
“…This may be due to more severe illness and more medical treatment and oxygen support associated with higher pulmonary opacity score. Previous evidence suggested that patients having bilateral pneumonia were hospitalized longer than those with normal CT scan results [ 12 ] and patients with higher CT scores may have more prolonged disease course and hospital stay [ 21 , 46 , 47 ]. Our study did not assess the association between pulmonary opacity score and mortality because of no recorded death in the study sample as a result of early recognition and intervention [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be due to more severe illness and more medical treatment and oxygen support associated with higher pulmonary opacity score. Previous evidence suggested that patients having bilateral pneumonia were hospitalized longer than those with normal CT scan results [ 12 ] and patients with higher CT scores may have more prolonged disease course and hospital stay [ 21 , 46 , 47 ]. Our study did not assess the association between pulmonary opacity score and mortality because of no recorded death in the study sample as a result of early recognition and intervention [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…CT findings of COVID-19 are mainly patchy glass opacity in the peripheral area [ 6 , 7 ]. Previous studies have shown that the abnormal imaging of COVID-19 patients was correlated with main clinical symptoms [ 8 ], demographic, epidemiologic, clinical, laboratory characteristics, treatments, severe/critical pneumonia [ 9 ], maximal respiratory severity score [ 10 ], intensive care unit (ICU) admission [ 11 ], and length of hospitalization [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…With components all over the spectrum, WGN is a kind of simulation noise suitable for signal-noise separation. In recent years, the influence of WGN has been considered in many fields-for example, the influence of time delay and noise on the electrical activity of neurons [13], noise suppression ability of the scale-free spiking neural network (SFSNN) with high and low average clustering coefficients (ACC) under WGN [14], the application of Gaussian approximation in gene expression models [15], the combined effects of phase and WGN in the performance of radio over fiber-orthogonal frequency division multiplexing (ROF-OFDM) schemes [16], WGN image denoising based on edge detection [17], and so on. The abovementioned research shows that WGN as simulation signal applies to physical, chemical and biological systems well.…”
Section: Introductionmentioning
confidence: 99%